Phenobarbital loaded microemulsion: development, kinetic release and quality control - Kayo Alves Figueiredo; Jamilly Kelly Oliveira Neves; José Alexsandro da Silva; Rivelilson Mendes de Freitas; André Luis Menezes Carvalho
ABSTRACT This study aimed to obtain and characterize a microemulsion (ME) containing phenobarbital (PB). The PB was incorporated in the proportion of 5% and 10% in a microemulsion system containing Labrasol(r), ethanol, isopropyl myristate and purified water. The physicochemical characterization was performed and the primary stability of the ME was evaluated. An analytical method was developed using spectrophotometry in UV = 242 nm. The kinetics of the in vitro release (Franz model) of the ME and the emulsion (EM) containing PB was evaluated. The incorporation of PB into ME at concentrations of 5 and 10% did not change pH and resistance to centrifugation. There was an increase in particle size, a decrease of conductivity and a change in the refractive index in relation to placebo ME. The ME remained stable in preliminary stability tests. The analytical method proved to be specific, linear, precise, accurate and robust. Regarding the kinetics of the in vitro release, ME obtained an in vitro release profile greater than the EM containing PB. Thus, the obtained ME has a potential for future transdermal application, being able to compose a drug delivery system for the treatment of epilepsy.